Some aspects of the personal legal status in the Roman army with special regard to the period of the III century AD - Nedyalkov, Nikolay (Cultura giuridica e diritto vivente, 2020)
[Some aspects of the personal legal status in the Roman army with special regard to the period of the III century AD]. The presented article covers a few issues that could be linked to the general topic of the personal status in the Roman army with a special regard for the period of transition towards the Late Antiquity – III century AD. An analysis is made of the different types of discharge from the army and the veteran’s certificate, given to the former soldiers. Some of the privileges, brought by this certificate upon the receiver are further researched, including the fact that it was a specific way of real estate acquisition. The second part of the article deals with the effect of military awards on the personal status and includes a short overview of their development through the centuries. Conclusions are made based on the analysis.